Prevalence and treatment of spontaneous intracranial artery dissections in patients with acute stroke due to intracranial large vessel occlusion. (6th March 2018) - Labeyrie, Marc-Antoine; Civelli, Vittorio; Reiner, Peggy; Aymard, Armand; Saint-Maurice, Jean-Pierre; Zetchi, Akli; Houdart, Emmanuel
Abstract : Objective: To identify the prevalence and therapeutic consequences of spontaneous intracranial artery dissection (IAD) at the acute phase of ischemic stroke. Methods: We reviewed clinical and imaging data of consecutive patients attending our center for mechanical thrombectomy (MT) between January 2012 and November 2017. IAD was defined according to published criteria and our own angiographic criteria (no clot following MT, and normalization of the vessel caliber after stenting). Results: IAD was retrospectively diagnosed in 13/391 (3%) patients (inter-rater agreement κ=0.885, P<0.001). It was an extending of extracranial dissection in 7/13 (54%) patients. A total of 21 recanalization approaches (with or without IV tissue plasminogen activator) were analyzed in 13 patients. A medical approach was used in 7/21 (33%), MT in 7/21 (33%) (stent retriever=6, thromboaspiration=1), and permanent stenting in 7/21 (33%). A rescue recanalization was necessary after 8/14 (57%) approaches without stenting. Stenting was associated with a best rate of recanalization (P=0.001) and with a trend towards a lower rate of ischemic recurrence (P=0.057). Stenting of a circulating false lumen failed to recanalize the artery in two patients. At the last follow-up, no patient had developed a subarachnoid hemorrhage due to the dissection. The outcome at 3 months was favorable in 8/13 (62%) patients. One patient died at 3 weeks owing to a severe cerebellar infarction. Conclusion: IAD is a rare diagnosis that should be systematically considered in patients with intracranial large vessel occlusion, especially in patients with extracranial artery dissection and when MT does not retrieve any clot. Stenting of IAD as first-line approach should be assessed in further studies.